Constitutional Protection of the Environment and Future Generations: Legislation and Practice in Certain Central European Countries - Szilágyi, János Ede (2022)
The book ’Constitutional Protection of the Environment and Future Generations’ reviews the constitutional legislation and constitutional practice of some Central European countries. In the context of constitutional practice, the case law of the constitutional courts of the countries concerned is primarily, but not exclusively, analysed. The book is basically divided into two parts. The first part consists of two chapters. The first chapter reviews the concepts, legal and moral dimensions of 'sustainable development' and 'the interests of future generations'. In the second chapter, environmental issues are analysed in the light of the European human rights system, with a Central European perspective. In the second part of the book, invited authors from the countries concerned review the protection of the environment and future generations in their constitutions and constitutional jurisprudence. The countries concerned are: the Visegrad Four, Romania, Slovenia, Croatia and Serbia. The final chapter of the second part is a summary chapter in which the legislation of the eight countries concerned is analysed in a comparative perspective. An important aim of the book is to identify good practices and to formulate de lege ferenda recommendations.